Nitrogen and phosphorus nutrition of cattle [ reducing the environmental impact of cattle operations - Hristov, Alexander; Pfeffer, Ernst (CABI, 2005)
There are tremendous benefits to feeding ruminants nitrogen and phosphorus supplements, in terms of milk production and productivity. However, what goes in must come out. Nitrogen and phosphorus excretions from dairy cattle are a major environmental polutant.